The Effect of The Beyond Center and Circles Time (Bcct) Method on The Social Ability of Children Aged 5-6 Years at PGRI Bandarjaya Kindergarten - Santa Idayana Sinaga; Eri Susanti (Journal on Education, 2023)
This study aims to determine "The Effect of the Beyond Center And Circles Time (BCCT) Method on the Social Abilities of Children Aged 5-6 Years at TK PGRI Bandarjaya. The problem that researchers encountered in this study is Is There an Effect of the Beyond Center And Circles Time (BCCT) Method on the Social Abilities of Children Aged 5-6 Years in Kindergarten PGRI Bandarjaya. researchers used the Pre-Experimental method using the One-Group Pretest-Posttest Design. Data collection techniques for this research are observation, interviews, and documentation. The population is 47 children and a sample of 25 children in group B class. Based on the calculations which were carried out from the results of the posttest normality of the data, the homogeneity of variance can be shown from the results of the hypothesis calculations. In addition, the next step is to test the hypothesis after which it is ensured that the homogeneity of the data is normal and the variance in the study is homogeneous and the data is normally distributed. The research hypothesis states that there is a significant effect of the use of the Beyond Center And Circles Time (BBCT) method on the social abilities of children aged 5 to 6 years at TK PGRI Bandarjaya. From the results of the t-test calculation above it is known that the value of tcount>ttable or 33.717>2.064 means that Ho is rejected and Ha is accepted